What we can and cannot see from the surveillance for drug-resistant Pseudomonas aeruginosa—Findings from the evaluation of a surveillance system for multidrug-resistant P. aeruginosa infections in Japan - Shogo Otake; Takuya Yamagishi; Takayuki Shiomoto; Manami Nakashita; Hitomi Kurosu; Chiaki Ikenoue; Hirofumi Kato; Munehisa Fukusumi; Tomoe Shimada; Takuri Takahashi; Motoi Suzuki; Teruo Kirikae; et al. (PLoS ONE, 2025)
Introduction Antimicrobial resistance in Pseudomonas aeruginosa is one of the global health concerns. Like many countries, Japan monitors multidrug-resistant P. aeruginosa (MDRP) infections through a national sentinel surveillance system, which has shown a recent decline in MDRP reports. We evaluated this surveillance system to verify the validity of this trend and explore future directions. Methods We conducted a cross-sectional mixed-method study based mainly on the guidelines published by the United States Centers for Disease Control and Prevention in 2001. As a quantitative method, we analyzed characteristics of reports on MDRP infections from designated sentinel sites (DSSs) between 2013–2022. A questionnaire was sent to identifiable DSSs (target DSSs) requesting data on accurate numbers of MDRP infections between 2018–2022 to assess attributes such as geographical representativeness. Additionally, we conducted as a qualitative method face-to-face, semi-structured key informant interviews with surveillance system stakeholders to assess its usefulness and challenges. Results From 2013 to 2022, 1,666 cases of MDRP infections were reported by 463 target DSSs, which were scattered across the county. We obtained valid responses to the questionnaire survey from 231 target DSSs (49.9%). From 2018 to 2022, these sites reported 277 cases as MDRP infections, while 184 cases were accurate cases of MDRP infection, with both numbers declining over time. False reporting and underreporting of MDRP infections were common, resulting in a positive predictive value of 0.45 and a sensitivity of 0.65 for the reports of MDRP infections to the surveillance system. The interviews highlighted the difficulties in timely detection, accurate reporting, and international data comparison. Conclusion Our evaluation indicated that the current sentinel surveillance system for MDRP infections partially captured the true decreasing trend in Japan. However, as the epidemiology of drug-resistant P. aeruginosa is changing, national policy and surveillance strategies would need to address changing public health needs.